CTE in Athletes: Understanding the Long-Term Effects of Repetitive Head Injuries - Sepioło, Weronika; Lewandoswki, Mikołaj; Kwiatkowska, Zofia; Kurkiewicz, Wojciech; Woźniak, Oskar; Mikulska, Jowita; Wąsik, Joanna; Gryboś, Kacper; Kiełbratowska, Julia (Quality in Sport, 2025)
Introduction and Purpose Chronic traumatic encephalopathy (CTE) is a progressive neurodegenerative disease linked to repeated head injuries such as concussions and sub-concussive impacts [19]. Initially observed in retired boxers with behavioral and cognitive symptoms, it was called “punch-drunk syndrome” [3,9,16]. CTE is mostly found in athletes from contact sports (e.g., football, boxing, hockey, rugby) and in military personnel [1,3,9,13,19]. While most reported cases involve male athletes, anyone exposed to repetitive head injury (RHI) is at risk [2,10,13]. Due to increasing awareness of its long-term effects on brain health, CTE is now a critical topic in sports medicine, neurology, and public health. Material and Methods A literature review was conducted using PubMed, focusing on studies published up to the end of 2023. Keywords included: “CTE in athletes,” “repetitive head impacts,” “tau protein,” “encephalopathy,” and “CTE.” Studies were selected based on their focus on long-term effects of RHI, CTE pathology, and prevention strategies. Results The review highlights the connection between repeated brain trauma and CTE in athletes. Ongoing research aims to uncover its biological mechanisms and develop early diagnostic tools and targeted treatments. Long-term studies tracking athletes are vital for identifying causes and modifiable risk factors. Conclusions CTE illustrates the complex link between repeated head trauma and brain health decline. While progress has been made, diagnosis, treatment, and prevention remain difficult. Continued research and collaboration among clinicians, researchers, sports organizations, and policymakers are essential to reduce risks and protect athlete well-being.